Efficacy of different instruments for the identification of the nursing diagnosis spiritual distress - Erika de Cássia Lopes Chaves (Revista Latino-Americana de Enfermagem, 2011)
The study aims to identify the nursing diagnosis Spiritual distress in 120 patients with Chronic Renal Insufficiency, using different instruments, and to evaluate the effectiveness of these instruments in support of this identification. Data were collected separately by two nurses using a questionnaire containing sociodemographic information and the defining characteristics of Spiritual distress, as well as direct questioning to the patient regarding the presence of the diagnosis and the instruments: the Spirituality Rating Scale; Pinto and Pais-Ribeiro's Spirituality Scale; and the Spiritual Well-being Scale. The study found that 25.8% to 35.8% of the patients had the diagnosis. The diagnostic evaluation developed by the expert nurses presented no divergence between the two and obtained a perfect concordance coefficient (96.7%) with the opinion of the patient; this demonstrated substantial concordance with the Existential Well-being Sub-scale (83.3%) and with the Pinto e Pais-Ribeiro's Spirituality Scale (87.5%), which demonstrated their usefulness for diagnostic identification.